The anterior inferior cerebellar artery abutment: an uninvited guest in sudden sensorineural hearing loss - Gowda, Vishwanath; Rai, Akash; V., Manishaa E.; Havaldar, Rajesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Sudden sensorineural hearing loss (SSNHL) is an otological emergency and prompt recognition and management has been shown to improve hearing outcomes and quality of life. A 49-year-old female presented to the ENT OPD with complaints of sudden onset decreased hearing in the right ear since 3 days. Pure tone audiometry done in an outside hospital on day 2 of patient’s complaints showed right ear to have pure tone average of 90 dB (profound hearing loss) and left ear to have pure tone average of 21.66 dB (within normal limits). At presentation to the ENT OPD on day 3 of complaints, otoscopic examination revealed normal tympanic membrane. MRI inner ear and brain (plain and contrast) showed the right anterior inferior cerebellar artery to be abutting the posterior aspect of vestibulocochlear nerve. Patient received 2 doses of intratympanic injection of Dexamethasone followed by a course of oral steroids for 15 days. Serial repeat pure tone audiometry showed marked improvement of symptoms. Although most cases of SSNHL are idiopathic, a number of treatable conditions do exist. The relationship between vascular loops around the vestibulocochlear nerve and sudden sensorineural hearing loss have to be kept in mind while evaluating these patients. Prognosis for hearing recovery is based on several factors, including time since onset, degree of deafness, age, and vertigo. Although SSNHL will often spontaneously improve without treatment, directed therapy against treatable causes along with steroid therapy can aid in the improvement of symptoms.